2011
DOI: 10.1530/eje-11-0482
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of androgen concentration in women: liquid chromatography–tandem mass spectrometry and extraction RIA show comparable results

Abstract: Objective: The measurement of serum testosterone in women is challenging due to lack of trueness, precision, and sensitivity of various available testosterone assays. Accurate assessment of testosterone in women is crucial especially in conditions associated with alleged over-or under-production of testosterone, such as in polycystic ovary syndrome (PCOS) or primary ovarian insufficiency (POI). The aim of this study was to measure and compare androgen concentrations in women with PCOS, POI, and female controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 41 publications
3
40
0
3
Order By: Relevance
“…In the present study carried out in postmenopausal women, we observed a small but significant increase in the levels of circulating testosterone, reaching 1.1G0.2 nmol/l. Studies assessing the levels of testosterone in women of reproductive age by LC-MS/MS have reported the levels of circulating testosterone to be in the range of 0.1-2.8 nmol/l, with median levels of 0.9 nmol/l (36,37,38). Thus, this lowdose oral regimen did not cause androgen excess in peripheral blood.…”
Section: Discussionmentioning
confidence: 85%
“…In the present study carried out in postmenopausal women, we observed a small but significant increase in the levels of circulating testosterone, reaching 1.1G0.2 nmol/l. Studies assessing the levels of testosterone in women of reproductive age by LC-MS/MS have reported the levels of circulating testosterone to be in the range of 0.1-2.8 nmol/l, with median levels of 0.9 nmol/l (36,37,38). Thus, this lowdose oral regimen did not cause androgen excess in peripheral blood.…”
Section: Discussionmentioning
confidence: 85%
“…The vast majority of laboratories performing a total serum testosterone assay use direct methods without extraction before performing an immunoassay (48,49). In fact, most immunoassays yield values higher than those obtained using gas chromatography coupled with mass spectrometry (GC-MS) or liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS) (50,51), which are recommended as gold standard methods for evaluating steroid hormones (52,53).…”
Section: Laboratory and Biomarkersmentioning
confidence: 99%
“…Measurement of DHEAS, a hormone of predominantly adrenal origin in women, is not routinely required, although when a neoplastic source of androgen excess is suspected a very high DHEAS concentration may be predictive of an androgen-secreting adrenal cancer (19). The evaluation of steroid hormone profiles, by using liquid chromatography combined with tandem mass spectrometry, a recent technique displaying good precision, sensitivity, and high accuracy, would greatly improve the assessment of androgen excess in patients with PCOS (20,21,22,23).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%